The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1213/00000539-197809000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Pathology Following Short-Term Intubation with Low-and High-Pressure Endotracheal Tube Cuffs

Abstract: Histologic sections of dog tracheas were taken from 20 dogs anesthetized and intubated for 5 to 7 hours with high-pressure, low-volume Shiley or low-pressure, high-volume Lanz endo-tracheal tubes. Microscopic examination and measurement showed that while the high-pressure, low-volume cuff produced deeper average mucosal erosion, the large-volume, low-pressure cuff resulted in significantly greater lengths of tracheal mucosa-cuff erosion. Maximal depth of penetration throught the basement membrane was similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

1980
1980
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 0 publications
0
23
0
3
Order By: Relevance
“…Proposed causes of postoperative sore throat include: mucosal erosion by the tracheal tube cuffs ; mechanical trauma from intubation; and inflammation of the mucosa . Studies have suggested that various anti‐inflammatory and analgesic agents, such as inhaled corticosteroids , systemic corticosteroids , ketamine gargle , liquorice gargle , and topical benzydamine hydrochloride , could prevent postoperative sore throat.…”
Section: Introductionmentioning
confidence: 99%
“…Proposed causes of postoperative sore throat include: mucosal erosion by the tracheal tube cuffs ; mechanical trauma from intubation; and inflammation of the mucosa . Studies have suggested that various anti‐inflammatory and analgesic agents, such as inhaled corticosteroids , systemic corticosteroids , ketamine gargle , liquorice gargle , and topical benzydamine hydrochloride , could prevent postoperative sore throat.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews of the more common complications have been published, as also have comparisons of morbidity rates with various techniques and materials (Baron & Kohlmoos 1951, Blanc & Tremblay 1974, Bryce et al 1968, Kambic & Radsel 1978, McGovern et al 1971. Histological analyses of the lesions produced by intubation have been made with accuracy both quantitatively and qualitatively (Burns et al 1970, Hilding 1971, Loeser et al 1978. The respiratory function of the larynx and trachea is the sole physiological activity to have undergone similar scrutiny following intubation (Stewart et al 1980, Strong & Passy 1977.…”
Section: Introductionmentioning
confidence: 99%
“…During last decades, the wide distribution of high-volume low-pressure (Hi-Lo) ETTs, helping to avoid ETT cuff overinflation, has significantly reduced the frequency of ischemic tracheal lesions[19]. However, in a randomized controlled animal study where the efficacy of a pneumatic device for P cuff management was tested, no differences were identified in the prevalence of tracheal mucosa lesions between the two animal groups[20].…”
Section: Discussionmentioning
confidence: 99%